Pengaruh Peer Education terhadap Pengetahuan, Sikap dan Keterampilan Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri - Amin, Santi; Tini, Tini; Lushinta, Lidia (Midwifery Care Journal, 2025)
Â Breast cancer is second cause of death in women. The cases has increased so it is necessary to have early detection of breast cancer through Breast Self Examination (BSE) which needs to be done since they are teenagers, but many teenagers do not understand how to detect early breast cancer so they need education through peer education by utilizing peers to increase knowledge, attitudes and skills about BSE. The purpose of the study was to determine the effect of peer education on knowledge, attitudes and skills about BSE in high school grade 2 girls. This research uses a quasi-experimental with a non-equivalent control group pre-test post-test research design. The number of samples using a total sampling of 63 students. Measuring tools in the form of Standar Operational Procedur (SOP), observation sheets and questionnaires. Mann Whitney test data analysis. Results of the study showed there were differences in knowledge (p value 0.000), attitude (p value 0.000) and skills (p value 0.000) before and after the group that was given leaflets to female students at SMK Teluk Pandan. There is a difference in knowledge (p value 0.000), attitude (p value 0.000) and skills (p value 0.000) between those who are given peer education and those who are given leaflets. Providing peer education is more effective than leaflets. Peer education increases knowledge, attitudes and skills about BSE in young women.